Effects of Length to the Diameter Ratio on the Buckling Behavior of Cylinders under Axial Load - Kadhum, Ahmed Farhan (Al-Nahrain Journal for Engineering Sciences, 2018)
In this research the behavior of cylindrical shells under axial load have been studied. The experimental program is included two groups: the first consists of nine cylinders; each has a diameter of 150 mm, while the height varies from 100 to 500 mm and thickness of 1.5 mm, test results show that the optimum height to achieve the maximum strength is 300 mm with L/D equal to 2. The second group consists of two cylinders with diameter of 150 mm and height of 300 and 500 mm strengthened with stiffeners plate welding from inside at four quarters with thickness of 1.5 mm and width 20 mm fabricated from the same metal of the cylinders. After testing these two cylinders were gain an increase in the strength reached to 42% for 300 mm cylinder and 26.4% for 500 mm cylinder. The failure modes for these two groups are: the buckling at bottom like “elephant’s foot” for cylinders height from 100 to 300 mm and “inelastic buckling” for cylinders height from 350 to 500 mm for the first group, and the ” inelastic buckling” for the second group.